A higher order model for inelastic response of composite beams with interfacial slip using a dissipation based arc-length method. (15th May 2017) - Uddin, Md. Alhaz; Sheikh, Abdul Hamid; Brown, David; Bennett, Terry; Uy, Brian
Highlights: Inelastic response of steel-concrete composite beams is studied. The partial interaction due to interfacial slip between two layers is considered. A higher order beam theory is used to capture the cross-sectional warping. An efficient numerical model is developed to implement the proposed technique. A robust arc-length method is used to capture the post peak response. Abstract: An efficient one dimensional finite element model is developed for an accurate prediction of the inelastic response of steel-concrete composite beams with partial shear interaction using a higher-order beam theory (HBT). This is achieved by taking a third order variation of the longitudinal displacement over the beam depth for the two layers separately. The deformable shear studs used for connecting the concrete slab with the steel girder are modelled as distributed shear springs along the interface between these two material layers. A plasticity model based on von Mises yield criterion and a damage model are used to simulate the inelastic behaviour of beam materials. An arc-length method based on energy dissipation is employed to capture the post peak response successfully. The capability of the proposed model is assessed through its validation and verification using existing experimental results and numerical results produced by detailed finite element modelling of these beams.